ARCHITECTURAL AND TOWN-PLANNING HERITAGE OF THE KITABO-SHAKHRISABZ OASIS FROM ANTIQUITY TO THE BEGINNING OF THE XX CENTURY (RECONSTRUCTION ISSUES) - Гильманова Нафиса Валиахметовна (European Science Publishing, 2025)
This article examines the architectural and town-planning heritage of the Kitabo-Shakhrisabz oasis from antiquity to the beginning of the XX century, paying special attention to the reconstruction of the ancient archaeological sites of the region, including Uzunkyr, Sangirtepa and Padayataktepa.
Keywords: Shakhrisabz, Kitab, Uzunkyr, Sangirtepa, Padayataktepa, Kitabo-Shakhrisabz oasis.